PARADIGMA TEORI BELAJAR DAN MOTIVASI PEMBELAJARAN DI ERA INDUSTRI 4.0 - Maria Ulviani (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2017)
Learning theory suggests that the most important is input in the form of stimulus and output in the form of a response. Whereas what happens between stimulus and response is considered not important to note because it cannot be observed, only stimulus and response can be observed. This study uses a library research method to explore literature information about learning theory and learning motivation. The results of the study show that motivation is an important factor that influences student will, process, and learning outcomes. Motivation is formulated as a condition that makes a person have the will to achieve certain goals through the implementation of a task. Someone who is motivated tends to survive and is not easily discouraged in carrying out tasks. One motivational strategy in the learning process is by applying four principles of motivation, namely: attention (attracting and maintaining student attention), relevance (expressing the relevance of lectures to student needs), confidence (fostering and strengthening student confidence), satisfaction (efforts to do lecture activities in accordance with the interests, characteristics